Indifference and social fabric. when the letter creates borders (2014)
From a psychoanalytical perspective,the objective of this article isto discuss indifference as a positionwith respect to the Other, in orderto suggest that resorting to the letteris a result and a singular creationthat offers the subject a possibilityof creating ties, on the basis of alogic of openness and recognition ofalterity and difference. Situating thecause of indifference in the tensionbetween the Other and jouissancemakes it possible to address themodalities of participation and theawareness of the suffering of theothers as effects of insertion intothe social fabric, the logics that governits ordering, and the possibleinscription of the radical differenceof the subject. Jacques Lacan’s workon Pascal’s famous wager regardingthe inconsistency of the Other isused as a referent.